ENGINEERING PEDAGOGY AS THE BASE FOR TRAINING OF MODERN ENGINEERS AND ACADEMIC STAFF OF TECHNICAL UNIVERSITIES - Vyacheslav M. Prikhod'Ko; Zoya S. Sazonova (Moscow Polytechnic University, 2016)
In the paper we analyze the issues of professional preparation of engineers at Russian technical universities and the improvement of pedagogical staff qualification in the context of changing conditions. We focus on the role of engineering pedagogy and thepeculiarities of the contemporary stage.